2016
DOI: 10.5194/hess-2016-221
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does the GPM mission improve the systematic error component in satellite rainfall estimates over TRMM, an evaluation at a pan-India scale?

Abstract: Abstract. Last couple of decades have seen the outburst of a number of satellite based precipitation products with Tropical Rainfall Measuring Mission (TRMM) as the most widely used for hydrologic applications. Transition of TRMM into Global Precipitation Mission (GPM) promises enhanced spatio-temporal resolution along with upgrades in sensors and rainfall estimation techniques. Dependence of systematic error components in rainfall estimates of Integrated Multi-satellitE Retrievals for GPM (IMERG), and their v… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…With rapid advances in remote sensing technologies and climate system modelling in recent decades, spaceborne sensors and state-of-the-art numerical weather models have produced vast precipitation datasets with a near-global coverage and an unprecedented spatiotemporal resolution (Sunilkumar et al, 2016;Prakash et al, 2018). For example, the Integrated Multi-satellitE Retrievals for GPM (IMERG) product is now available at 0.1° spatial and 30-minute temporal resolutions, and is anticipated to play a growing role in hydrological and meteorological monitoring (Beria et al, 2017;Massari et al, 2020). One of the latest global atmospheric reanalysis products, ERA5 provides hourly estimates for a large number of atmospheric, land and oceanic climate variables, and exhibits substantial improvements comparing to its predecessor in many regions of the globe (Graham et al, 2019;Tang et al, 2020;Tarek et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…With rapid advances in remote sensing technologies and climate system modelling in recent decades, spaceborne sensors and state-of-the-art numerical weather models have produced vast precipitation datasets with a near-global coverage and an unprecedented spatiotemporal resolution (Sunilkumar et al, 2016;Prakash et al, 2018). For example, the Integrated Multi-satellitE Retrievals for GPM (IMERG) product is now available at 0.1° spatial and 30-minute temporal resolutions, and is anticipated to play a growing role in hydrological and meteorological monitoring (Beria et al, 2017;Massari et al, 2020). One of the latest global atmospheric reanalysis products, ERA5 provides hourly estimates for a large number of atmospheric, land and oceanic climate variables, and exhibits substantial improvements comparing to its predecessor in many regions of the globe (Graham et al, 2019;Tang et al, 2020;Tarek et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Prakash et al [2016] compared the IMERG rainfall product with the TMPA rainfall product and ground-based rainfall data during heavy rainfall events over the southwest India. Beria et al [2016] evaluated the IMERG rainfall with the TRMM-3B42 at basin scale, which is relevant in terms of water resources assessment for policy makers. All these studies concluded that the IMERG showed good capability to capture rainfall events.…”
Section: Introductionmentioning
confidence: 99%